THE VALUE OF PET/CT IN DETECTING COLORECTAL CANCER RECURRENCE IN PATIENTS WITH NEGATIVE CT FINDINGS - Spirov, Goran; Bundovska Kocev, Smiljana; Matveeva, Niki; Spirov, Vasilcho; Ugrinska, Ana (Journal of Morphological Sciences, 2021)
Computed tomography (CT) is widely accepted imaging modality used to detect recurrent colorectal cancer (CRC) in the routine follow up, though further imaging may be required. The objective of this research is to investigate the value of PET/CT in detecting colorectal cancer recurrence despite negative CT findings. A retrospective review of colorectal cancer patients referred for 18F-FDG PET/CT imaging to the University institute of positron emission tomography in Skopje, between July 2018 and January 2020. All of the patients had a stage III disease and were clinically suspicious of recurrence (elevated CEA or presence of symptoms) despite recent negative CT findings. Twenty one patients (10 women and 11 men, mean age 56.95) met the above criteria. In 6 patients (28%) cancer recurrence was detected. Negative PET/CT findings were reported in eleven patients and in only one patient (1/11, 9%) recurrence was detected within one year of PET/CT. Equivocal PET/CT finding were reported in three patients, further work-up proved metastasis. In eight (8/9, 88%) patients with abnormal level of CEA, PET/CT detected or initiated further work-up that led to malignancy detection. Patients with stage III CRC had the most positive PET/CT findings 4/7 (57%) compared to others. PET/CT could detect disease recurrence in patients when clinically suspicion persists in spite of negative CT findings. Elevated CEA and the primary tumor stage were dominant features of the patients with recurrent disease. Negative predictive value of PET/CT is high enough to reassure clinicians and reduce patient anxiety. Kew words :colorectal cancer, cancer recurrence, PER/CT, CEA, CT https://doi.org/10.55302/JMS2142057s